The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1252/jcej.20.335
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitized isomerization of norbornadiene for solar energy storage and supression of side reaction.

Abstract: Photosensitized isomerization of norbornadiene to quadricyclene was investigated by using several photosensitizers such as toluene, acetone, acetophenone, benzophenone and a-naphthoquinone. The effect of wavelength on the quantum yield of quadricyclene and on the energy conversion efficiency was measured by using spectroirradiator. The formation of byproduct polymer in the presence of photosensitizers was also studied. The formation of polymers during irradiation, which prevents the repeated use of energy stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…These benefits are to some extent hampered by the fact that the parent NBD does not absorb light above 267 nm [10] . Therefore, a triplet photosensitizer is necessary to facilitate the light‐induced isomerization of unsubstituted NBD to the energy‐rich QC [8a, 25] . During this work, we opted to utilize acetophenone as a photosensitizer.…”
Section: Resultsmentioning
confidence: 99%
“…These benefits are to some extent hampered by the fact that the parent NBD does not absorb light above 267 nm [10] . Therefore, a triplet photosensitizer is necessary to facilitate the light‐induced isomerization of unsubstituted NBD to the energy‐rich QC [8a, 25] . During this work, we opted to utilize acetophenone as a photosensitizer.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, acetophenone is ideal for this purpose. [5] Irradiation of am ixture of malonate 2 and 5mol %a cetophenone in diethyl ether resulted in the formation of the desired QC malonate. To our surprise the successive Bingel-Hirsch reaction with this malonate did not give the expected product.…”
Section: Resultsmentioning
confidence: 99%
“…[4] Hence, at riplet photosensitizer with E T (sensitizer) > E T (NBD),s uch as acetophenone or benzophenone, is neededt oe nable the isomerization of neat NBD to QC. [5] Alternatively,i th as been shown that, by functionalization of the NBD scaffold, it is possible to redshift the absorption and simultaneously increase the quantum yield. [6] However,f unctionalization of the NBD scaffoldnaturally is alwaysa ccompanied with an increased molecular weight and, therefore, al ower energy storage density.N ext to the photoisomerization, also the corresponding back reactionf rom QC to NBD mustb ec onsidered and optimized.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to direct chemical modification, different photophysical methods have also been explored, including the use of sensitizers [48][49][50][51] and more recently, the use of photon upconversion systems. The latter systems convert low-energy photons that otherwise cannot be absorbed by the molecules into higher-energy photons.…”
Section: Most Challenges and Solutionsmentioning
confidence: 99%